Association of increased basic salivary proline‐rich protein 1 levels in induced sputum with type 2‐high asthma. Issue 4 (10th March 2022) - Chen, Fengjia; Liang, Yuxia; Zeng, Zhimin; Du, Lijuan; Xu, Changyi; Guo, Yubiao; Xie, Canmao
Abstract: Background: The aim of this study is to reveal whether basic salivary proline‐rich protein BstNI subfamily 1 (PRB1) may be used as a diagnostic biomarker for type 2‐high asthma. Methods: PRB1 protein levels in the induced sputum of 67 subjects with asthma and 27 controls were determined by an enzyme‐linked immunosorbent assay. Correlation analyses between PRB1 in the induced sputum and airway inflammatory indicators were also performed. Results: PRB1 protein levels were significantly upregulated in the induced sputum of asthmatic patients ( p  =0.0098) and correlated with clinical eosinophil‐related indicators and type 2 airway inflammation. These results indicate that PRB1 is a promising biomarker for type 2‐high asthma. Conclusions: The expression of PRB1 in induced sputum is a potential biomarker for type 2‐high asthma. The results of this study present new insights into the diagnosis and treatment of asthma. Abstract : Our study suggests that proline‐rich protein BstNI subfamily 1 (PRB1) expression in induced sputum is increased in asthmatic subjects, which demonstrates its association with type 2‐high asthma. Thus, PRB1 may be a biological marker for type 2‐high asthma. The findings of this study could provide new insights into the diagnosis and treatment of asthma.